2000
DOI: 10.1074/jbc.275.13.9441
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Peroxisomal Glycerolipid-synthesizing Enzymes during Differentiation of 3T3-L1 Adipocytes

Abstract: The glycerophosphate backbone for triglyceride synthesis is commonly believed to be created through the conversion of dihydroxyacetone phosphate (DHAP) by glycerophosphate dehydrogenase (GPD) to sn-glycerol 3-phosphate (GP), which is then converted by glycerophosphate acyltransferase (GPAT) to 1-acyl-GP. Consistent with this, GPD and GPAT are highly induced during differentiation of mouse 3T3-L1 preadipocytes. While the acyl dihydroxyacetone phosphate (acyl-DHAP) pathway for glycerolipid synthesis is commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 47 publications
(49 reference statements)
5
49
1
Order By: Relevance
“…Second, overexpression of peroxisomal DHAPAT activity in the NRel-4.15 transfectant did not result in increases in plasmalogen biosynthesis or increase their levels above normal. These results are in agreement with the observation that plasmalogen levels are not increased in differentiating 3T3-L1 cells, in which DHAPAT is induced several-fold (16).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Second, overexpression of peroxisomal DHAPAT activity in the NRel-4.15 transfectant did not result in increases in plasmalogen biosynthesis or increase their levels above normal. These results are in agreement with the observation that plasmalogen levels are not increased in differentiating 3T3-L1 cells, in which DHAPAT is induced several-fold (16).…”
Section: Discussionsupporting
confidence: 82%
“…The regulation of plasmalogen biosynthesis is likely to be complex and linked to the biosynthesis of nonether glycerolipids, because later steps in the pathway are also used in the synthesis of diacyl phospholipids and triglycerides (1). Recent evidence also suggests that dihydroxyacetonephosphate acyltransferase (DHAPAT), which catalyzes the first step in plasmalogen biosynthesis, may play a significant role in nonether glycerolipid biosynthesis as well; this activity is increased several-fold during the differentiation of 3T3-L1 cells to adipocytes (16). Therefore, the role of DHAPAT in the synthesis of this latter group of glycerolipids (nonether) remains to be determined.…”
mentioning
confidence: 99%
“…Indeed, we found that many adipogenic markers were upregulated during adipogenesis, e.g. several transcription factors (C/EBP␣, PPAR␄, RXR␣, SREBP-1), enzymes involved in fatty acid and TG metabolism (DHAPAT,FABP4/aP2,FAS,GPAT,SCD1,SCD2), and adipokines (AGT, resistin) (MacDougald and Lane, 1995;Gregoire et al, 1998;Burton et al, 2004;Hajra et al, 2000;Song et al, 2002). We also observed the downregulation of anti-adipogenic markers, such as Pref-1, an autocrine and/or paracrine inhibitor of adipogenesis, and the transcription factors GATA-2 and GATA-3.…”
Section: Journal Of Cell Science 119 (7)mentioning
confidence: 99%
“…These studies found that the mitochondrial isoform accounts for ?50% of total GPAT activity in rat liver and is significantly decreased upon fasting (27,28). The microsomal isoform is the major isoform in brown and white adipose tissue, accounting for 80-90% of total GPAT activity (29,30), and is dramatically upregulated during adipocyte differentiation (16,31,32). Microsomal GPAT is also the major isoform in heart (?70% of total activity) (33,34), and in brain (35).…”
Section: Tissue Distribution and Regulation Of Gpat Isoforms As Definmentioning
confidence: 99%
“…This pathway is thought to be of only minor quantitative importance for the formation of triglycerides and glycerophospholipids in most tissues, and functions primarily in the formation of ether phospholipids, as demonstrated by studies in tissue culture cells as well as by mutational analysis in mice and humans (11)(12)(13)(14)(15). However, it can contribute significantly to glycerolipid formation under certain circumstances (e.g., in differentiated 3T3-L1 adipocytes after an overnight culture in glucose-free medium) (16). It is also noteworthy that diacylglycerol can be produced via the monoacylglycerol pathway in a GPAT-independent manner.…”
mentioning
confidence: 99%